Paradigma Perlindungan Hak Cipta bagi Pencipta Lagu di Luar Sistem Kolektif Nasional Indonesia - Izzah Sulistyorini, Nurul (Jurnal Hukum In Concreto, 2024)
Legal protection of copyright is a form of state recognition of the exclusive rights of creators over their intellectual works. In practice, Indonesia’s copyright protection system for musical works is implemented through a collective management mechanism regulated under Law Number 28 of 2014 and operationalized by Collective Management Organizations (LMK) and the National Collective Management Organization (LMKN). Nevertheless, this system has not ensured equal legal protection for independent songwriters outside the collective structure. This research aims to identify normative and institutional gaps in the current protection model and to formulate a reform-oriented legal framework that promotes inclusivity and non-discrimination. The research method applied is normative legal research using statutory and conceptual approaches. The findings reveal that independent creators continue to face limited access to royalty distribution, lack of alternative protection schemes, and suboptimal use of information technology in copyright registration and distribution. Accordingly, a reformulation of the copyright protection system is required through the integration of digital infrastructure, simplification of administrative procedures, and the inclusion of non-collective authors in the national copyright regime.